Biological responses according to the shape and size of carbon nanotubes in BEAS-2B and MESO-1 cells - Haniu H (Dove Medical Press, 2014)
Hisao Haniu,1,2 Naoto Saito,2,3 Yoshikazu Matsuda,4 Tamotsu Tsukahara,5 Yuki Usui,1,6,7 Kayo Maruyama,2,3 Seiji Takanashi,1 Kaoru Aoki,1 Shinsuke Kobayashi,1 Hiroki Nomura,1 Manabu Tanaka,1 Masanori Okamoto,1 Hiroyuki Kato1 1Department of Orthopaedic Surgery, Shinshu University School of Medicine, Nagano, Japan; 2Insutitute for Biomedical Sciences, Shinshu University, Nagano, Japan; 3Department of Applied Physical Therapy, Shinshu University School of Health Sciences, Nagano, Japan; 4Clinical Pharmacology Educational Center, Nihon Pharmaceutical University, Saitama, Japan; 5Department of Hematology and Immunology, Kanazawa Medical University, Ishikawa, Japan; 6Research Center for Exotic Nanocarbons, Shinshu University, Nagano, Japan; 7Aizawa Hospital, Sports Medicine Center, Nagano, Japan Abstract: This study aimed to investigate the influence of the shape and size of multi-walled carbon nanotubes (MWCNTs) and cup-stacked carbon nanotubes (CSCNTs) on biological responses in vitro. Three types of MWCNTs – VGCF®-X, VGCF®-S, and VGCF® (vapor grown carbon fibers; with diameters of 15, 80, and 150 nm, respectively) – and three CSCNTs of different lengths (CS-L, 20–80 µm; CS-S, 0.5–20 µm; and CS-M, of intermediate length) were tested. Human bronchial epithelial (BEAS-2B) and malignant pleural mesothelioma cells were exposed to the CNTs (1–50 µg/mL), and cell viability, permeability, uptake, total reactive oxygen species/superoxide production, and intracellular acidity were measured. CSCNTs were less toxic than MWCNTs in both cell types over a 24-hour exposure period. The cytotoxicity of endocytosed MWCNTs varied according to cell type/size, while that of CSCNTs depended on tube length irrespective of cell type. CNT diameter and length influenced cell aggregation and injury extent. Intracellular acidity increased independently of lysosomal activity along with the number of vacuoles in BEAS-2B cells exposed for 24 hours to either CNT (concentration, 10 µg/mL). However, total reactive oxygen species/superoxide generation did not contribute to cytotoxicity. The results demonstrate that CSCNTs could be suitable for biological applications and that CNT shape and size can have differential effects depending on cell type, which can be exploited in the development of highly specialized, biocompatible CNTs. Keywords: multi-walled carbon nanotube, cup-stacked carbon nanotube, cytotoxicity, in vitro, intracellular acidity